2017
DOI: 10.1039/c7fd00116a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular chiral self-assemblies of Gly–Pro dipeptides on metallic fcc(110) surfaces

Abstract: The adsorption of the Glycine-Proline (Gly-Pro) dipeptide has been investigated by surface science complementary techniques on Au(110) and Ag(110), showing some interesting differences both in the chemical form and surface organization of the adsorbed peptide. On Au(110), Gly-Pro mainly adsorbs under a neutral form (COOH/NH2), at low coverage or for short time of interaction ; the surface species become zwitterionic for higher coverage or longer time of interaction. These changes are accompanied by a complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The red and green arrows represent the crystallographic orientations of self-assembled L-M6 and D-M6 peptides, respectively. We found that the chiral index (6,5) is the closest to the red line of L-M6 peptides, based on the relationship between the angle and chiral index (Figure S2). The orientation of the D-M6 peptide ordered nanostructures correspond to a chiral index of (5,6).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The red and green arrows represent the crystallographic orientations of self-assembled L-M6 and D-M6 peptides, respectively. We found that the chiral index (6,5) is the closest to the red line of L-M6 peptides, based on the relationship between the angle and chiral index (Figure S2). The orientation of the D-M6 peptide ordered nanostructures correspond to a chiral index of (5,6).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…We found that the chiral index (6,5) is the closest to the red line of L-M6 peptides, based on the relationship between the angle and chiral index (Figure S2). The orientation of the D-M6 peptide ordered nanostructures correspond to a chiral index of (5,6). Both the self-assembly of L-M6 and D-M6 peptides have mirror symmetry along the armchair direction.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The change in the chemical functionality of amino acid molecules adsorbed on sputtered surfaces with time has not been previously reported for any other surface. 31,32 During the chemical evolution process, the N 1s peak varies remarkably; the relative intensities of the two components are reversed ( Table 1). A summary of the XPS results, that is, the C 1s, N 1s and O 1s core-level peaks, ratios and component assignments, for the glycine/pyrite (monosulfide-enriched) system obtained at different evolution times under UHV is given in Table 1.…”
Section: Spectroscopy Evidenced Chemical Evolution Of Glycine On Pyrimentioning
confidence: 99%
“…Finally, another key parameter that influences the adsorption mode and subsequently the supramolecular assemblies of a given molecule is the chemical nature of the adsorbed species. We have shown recently that it is possible to tune adsorption mode, geometry and supramolecular assemblies of a given molecule by changing its deposition method: from the gas phase or from an aqueous solution [10][11][12]. The latter is achievable if an Electrospray Ionization (ESI) device is employed, instead of a traditional Knudsen cell.…”
Section: -Introductionmentioning
confidence: 99%